RANCANGAN SISTEM INFORMASI DATA INVENTORY PADA RESTU CELULARRANCANGAN SISTEM INFORMASI DATA INVENTORY PADA RESTU CELULAR - Elzas - (JURNAL AKADEMIKA)
This research was conducted in Restu Celular Bengkal River by suggesting some formulation problems, namely how the data processing on Restu Celular Inventory. With the aim to find out how the inventory data processing, as well as designing an application system that can cope with problems in data processing, in order to provide information that is accurate and fast. In this study the author uses Data Flow Diagrams (DFD) as an aid in the design of the system. Inventory data processing system implemented is still done manually. It is necessary for the development of the system by applying a programming language Visual Basic 6.0 with Microsoft Access Database design in data processing in order to produce timely and accurate information that can assist management in making decisions.